The interaction of Adipose Derived Stem Cells and Breast Cancer - Natasha Cunningham; Ava O'Meara; Cathy L. Brougham (SURE Journal: (Science Undergraduate Research Experience Journal))
Introduction: Mesenchymal stem cells are adult stem cells capable of self-renewal and multilineage differentiation (Schweizer et al., 2015). Adipose derived stem cells have been used in breast reconstruction following surgical intervention in breast cancer patients. MicroRNAs have been linked to gene regulation essential in oncogenic, and tumour suppression as well as cell signalling pathways in BC. Aim: To research the hypothesis of ADSCs and their therapeutic properties in BC patients. Methods: Proliferation assays were carried out to demonstrate how ADSC conditioned media influenced BC cell lines MDA-MB-231, SKBR3, and T47D. The expression of six miRNAs (miR-21, miR-133, miR-222, miR-146, miR-221, and miR-A) and three cytokines (TGF-β, RANTES, TNF- α) was determined using a variety of functional assays. Statistical analysis was performed using Minitab 20.1.0. Findings: Upregulation of miRNA expression all miR-21 co-culture samples, miR-222 T47D co-culture, and both miR-146, and miR-221’s SKBR3 BC co-culture cell line. All co-culture cells within miR-133 expression displayed downregulation of high significance, and co-culture cells lines MDA-MB-231 and SKBR3 expressing miR-222. Down-regulation was observed in all cytokine samples (p) of BC cell co-cultures, apart from RANTES concentration within SKBR3 (p). This research demonstrated how ADSCs have properties as a double-edged sword by providing insight upon ADSCs influence on BC malignancy properties. Which in future could be a target for novel treatment therapies, thus giving patients a better prognosis and survival rate by providing a personalised molecular approach of treatment.